Combustion and emission characteristics from biojet fuel blends in a gas turbine combustor. (1st September 2019) - Sundararaj, Ramraj H.; Kumar, Roshan Dinesh; Raut, Anoop Kumar; Sekar, T. Chandra; Pandey, Vivek; Kushari, Abhijit; Puri, S.K.
Abstract: Fossil fuels are non-renewable resources that will be depleted within the next century, leading to an energy crisis in the near future. Furthermore, there has been a global focus on emissions and its effect on the climate. The aviation sector stands out as a unique sector because a substantial amount of its emissions are injected at cruise altitude giving increased effectiveness to the pollutants. Biofuels (BF) derived from Jatropha and Camelina feedstocks are considered as one of the near-term solutions to the fuel crisis. The objective of this research is to study the effect of using different biofuel blends on gas turbine emissions and performance. These are blended in varying concentrations with conventional Jet-A1 and tested in a can type combustor at two different operating conditions. The performance of the combustor for these blends was evaluated by determining the combustion efficiency, temperature rise, and the emission indices. The general trend observed is that with increasing amounts of Camelina in the blends, there is an appreciable decrease in Carbon Monoxide (CO), Unburnt Hydrocarbons (UHC) and soot. However, the Nitrogen Oxides (NOx) emission increases slightly due to the higher combustion temperatures for Camelina based blends. The Jatropha-based fuels show a mixed trend even though they have comparable properties to the Camelina based fuels. Highlights: Experimental testing of liquid biofuel and Jet A1 blends that meet ASTM norms for aviation fuel. Emission and performance measurement in a practical gas turbine combustor. Biofuels used are derived from Camelina (UOP-SPK) and Jatropha (HEFA). CO, UHC and soot emissions decrease with increasing quantity of Biofuel in blend. Biofuels derived from these sources can be used as 'drop-in' fuels.